Exploring the potential of decentralized extension models on the sustainability of livelihoods: a food security lens on aquaculture farmers in Bangladesh - Dompreh, Eric Brako; Manyise, Timothy; Lozano Lazo, Denise; Khondker, Murshed-e-Jahan; Lam, Rodolfo Dam; Rossignoli, Cristiano M. (Frontiers in Sustainable Food Systems, 2024)
Small-scale farmers in Bangladesh aquaculture face multiple challenges. Among these challenges are the inadequate supply of quality seed, limited credit access, poor availability of quality fish feed, land-use conflicts, the adverse effects of climate change, and the low adoption of best aquaculture management practices. These challenges spiral into low productivity, low incomes, and low food security of households. Extension has been seen as an important tool for technology and knowledge transfer, resulting in increased farm productivity and household food security. However, small-scale aquaculture farmers in Bangladesh lack access to critical extension service needed to improve productivity and their livelihoods. Using Propensity Score Matching, we test whether more decentralized extension systems yield similar food security outcomes as traditional extension models. Analysing data from 1,017 respondent, we find that decentralized extension models lead to improved food security of aquaculture households compared to non-beneficiaries. We recommend among others, the critical need to synergize extension systems, reduce costs and better target aquaculture farmers. Additionally, public-private partnerships can help leverage strengths from various extension approaches for more effective knowledge dissemination to aquaculture farmers, ultimately enhancing their livelihoods.